Kedudukan Perempuan Mulih Daha dalam Keluarga dan Akibat Hukum Terhadap Anak di Desa Adat Mengwitani - Putu Ayu Devi Kardila; I Nyoman Putu Budiartha; I Wayan Rideng (Warmadewa Press, 2021)
Women who return to their original homes because of a divorce, their status is called mulih daha (girls return). With this, the mulih daha woman continues to carry out her swadharma (obligations) to her parents at her home. If the marriage breaks up due to divorce, it also has legal consequences for the child. Based on the background that has been described, the purpose of this study is to find out how the legal status of the Mulih Daha woman is and what are the legal consequences for the child brought by the Mulih Daha woman to her home. The research method in this writing uses empirical research methods. The results of this study indicate that mulih daha women have no right to claim back the right to inherit in their home of origin. The rights and obligations of parents who have divorced their children must still be carried out as stipulated in Article 26 paragraphs (1) and (2) of Law Number 35 of 2014 concerning amendments to Law Number 23 of 2002